2014
DOI: 10.1002/adem.201300450
|View full text |Cite
|
Sign up to set email alerts
|

Grain Boundary Phenomena in an Ultrafine‐Grained Al–Zn Alloy with Improved Mechanical Behavior for Micro‐Devices

Abstract: The microstructural and mechanical properties of an ultrafine-grained (UFG) Al-Zn alloy processed by high-pressure torsion (HPT) are investigated using depth-sensing indentations, focused ion beam, scanning electron microscopy and scanning transmission electron microscopy. Emphasis is placed on the microstructure and the effects of grain boundaries at room temperature. The experiments show the formation of Zn-rich layers at the Al/Al grain boundaries that enhance the role of grain boundary sliding leading to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 46 publications
(72 reference statements)
5
78
0
2
Order By: Relevance
“…1b). The abnormal softening of the high Znconcentrated Al-30Zn alloy is a consequence of the strong decomposition of the annealed microstructure in this alloy as shown earlier [4,5]. Recent transmission electron microscopy (TEM) and energy dispersive spectroscopy (EDS) results on grain boundaries (GBs) [4,6] showed that more than 50% of the Al/Al grain boundaries are wetted by Zn-rich layers (see Fig.…”
Section: Experimental Materials and Proceduresmentioning
confidence: 63%
See 2 more Smart Citations
“…1b). The abnormal softening of the high Znconcentrated Al-30Zn alloy is a consequence of the strong decomposition of the annealed microstructure in this alloy as shown earlier [4,5]. Recent transmission electron microscopy (TEM) and energy dispersive spectroscopy (EDS) results on grain boundaries (GBs) [4,6] showed that more than 50% of the Al/Al grain boundaries are wetted by Zn-rich layers (see Fig.…”
Section: Experimental Materials and Proceduresmentioning
confidence: 63%
“…Disks with diameters of 20 mm and thicknesses of 0.8 mm were homogenized at 500 o C for 1 h, then quenched into room temperature water and processed by HPT as described in [4][5][6]. Samples were cut from the half-radius of the HPT-processed disks.…”
Section: Experimental Materials and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with earlier reports concerning the effect of strain on phase transitions in Ti, [38][39][40] Zr, [41] ZrO 2 [30] and some other metallic alloys. [42][43][44] The cubic phase present after HPT processing remains partially stable even after pressure release because of the formation of nanograins. [19][20][21][22][23][24] Figure 4(b) shows Raman spectra for the samples processed for N = 0, 1 and 5 and subsequently sintered at 1,200°C for 2 h. Figure 4(b) suggests that the crystal structure of BTO samples is mainly composed of tetragonal phase after sintering at 1,200°C.…”
mentioning
confidence: 99%
“…By contrast, the HPT-induced dissolution of the nanoprecipitates that were initially present in the T6 peak-aged specimen favors the activation of GBS [17,26] and this produces a higher ductility and lower flow stress that may be useful for forming processes. It was reported earlier that the occurrence of GBS in an ultrafine grained Al-Zn alloys after HPT processing is favored by the presence of a solute-rich layer along the GBs [42,43]. However, it was not possible to detect these segregations in the present research because 15 any estimation by analytical TEM of low levels of segregation was severely hindered due to the similar atomic numbers of Si, Mg and Al [10].…”
Section: Discussionmentioning
confidence: 66%